Epistemological Analysis of Knowledge Management Implementation in Learning at IAIN Kediri - Yusuf, Moh. Asror; Arifin, Mohamad Zaenal (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2022)
Universities’ most valuable asset is knowledge, which drives their core objective: advancing knowledge. Effective knowledge management is crucial to foster innovation in higher education’s core activities. This study explores the implementation of knowledge management in learning at IAIN Kediri and provides an epistemological analysis. Using a qualitative approach, data were gathered from leaders at rectorate, faculty, and unit levels, as well as lecturers, through document analysis, questionnaires, in-depth interviews, and observations. The findings reveal that learning management at IAIN Kediri aligns with knowledge management principles, focusing on creating and disseminating knowledge among lecturers to improve learning outcomes. However, challenges remain, including fostering a culture of knowledge sharing, expanding IT facilities and human resources, and enhancing the online learning document storage system. These obstacles highlight areas for further development to optimize knowledge management practices and improve institutional learning outcomes.